Oesophageal motor events at the occurrence of acid reflux and during endogenous acid exposure in healthy subjects and in patients with oesophagitis. Issue 4 (April 1985) - Baldi, F; Ferrarini, F; Balestra, R; Borioni, D; Longanesi, A; Miglioli, M; Barbara, L
Abstract : In order to assess the oesophageal motor events associated with the occurrence of gastro-oesophageal acid reflux and those during endogenous acid exposure, we studied six healthy subjects and nine patients with symptoms and lesions of reflux oesophagitis. In the case of each subject simultaneous pressure and pH measurements of the distal oesophagus were taken both in fasting conditions and after a standardised balanced meal. Reflux episodes occurred in the absence of a lower oesophageal sphincter relaxation (34.3%, 17.7%) or in the presence of a relaxation associated (34.2%, 30.8%) or unassociated (31.5%, 51.5%) with a peristaltic sequence, in the controls and patients respectively. No significant differences were found between the two groups. During endogenous acid perfusion the distal oesophagus showed mainly a peristaltic motor activity, but the mean hourly number of peristaltic sequences was significantly lower in the patients than in the controls (33.5 +/- 27.2 vs 81.5 +/- 3.2, p less than 0.01). Our results show that the mechanisms of reflux are similar in controls and in patients, while the peristaltic frequency is reduced in the latter. This motor failure may be responsible for the increased reflux duration observed in patients with oesophagitis.